2022
DOI: 10.37497/rev.artif.intell.educ.v3i00.6
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of ChatGPT and its Implications for Education and Academic Research in the 21st Century

Altieres de Oliveira Silva,
Diego dos Santos Janes

Abstract: The rapid development of artificial intelligence (AI) technologies has led to the emergence of advanced language models like ChatGPT, which exhibit remarkable capabilities in generating human-like text. This article examines the transformative potential of ChatGPT and its impact on education and academic research in the 21st century. In the realm of education, ChatGPT offers personalized and interactive learning experiences, enabling students to engage in real-time conversations that enhance comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The following threats to the use of AI in higher education (Tambuskar, 2022) have been identified: lack of understanding of the context, threat to academic integrity, and perpetuation of discrimination in education, democratisation of plagiarism, and reduction of high-level cognitive skills (Farrokhnia et al, 2023). Researchers have found that the use of ChatGPT (Silva & Janes, 2022) can lead to writing texts that look plausible but are not true. This is also due to the fact that reliable information sources were not used when developing and setting up the ChatGPT (Fütterer et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The following threats to the use of AI in higher education (Tambuskar, 2022) have been identified: lack of understanding of the context, threat to academic integrity, and perpetuation of discrimination in education, democratisation of plagiarism, and reduction of high-level cognitive skills (Farrokhnia et al, 2023). Researchers have found that the use of ChatGPT (Silva & Janes, 2022) can lead to writing texts that look plausible but are not true. This is also due to the fact that reliable information sources were not used when developing and setting up the ChatGPT (Fütterer et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%